Moxifloxacin Liposomes: Effect of Liposome Preparation Method on Physicochemical Properties and Antimicrobial Activity against Staphylococcus epidermidis - Evangelos Natsaridis; Foteini Gkartziou; Spyridon Mourtas; Marc C. A. Stuart; Fevronia Kolonitsiou; Pavlos Klepetsanis; Iris Spiliopoulou; Sophia G. Antimisiaris (MDPI AG, 2022)
The aim of this study was the development of optimal sustained-release moxifloxacin (MOX)-loaded liposomes as intraocular therapeutics of endophthalmitis. Two methods were compared for the preparation of MOX liposomes; the dehydration-rehydration (DRV) method and the active loading method (AL). Numerous lipid-membrane compositions were studied to determine the potential effect on MOX loading and retention in liposomes. MOX and phospholipid contents were measured by HPLC and a colorimetric assay for phospholipids, respectively. Vesicle size distribution and surface charge were measured by DLS, and morphology was evaluated by cryo-TEM. The AL method conferred liposomes with higher MOX encapsulation compared to the DRV method for all the lipid compositions used. Cryo-TEM showed that both liposome types had round vesicular structure and size around 100-150 nm, while a granular texture was evident in the entrapped aqueous compartments of most AL liposomes, but substantially less in DRV liposomes; X-ray diffraction analysis demonstrated slight crystallinity in AL liposomes, especially the ones with highest MOX encapsulation. AL liposomes retained MOX for significantly longer time periods compared to DRVs. Lipid composition did not affect MOX release from DRV liposomes but significantly altered drug loading/release in AL liposomes. Interestingly, AL liposomes demonstrated substantially higher antimicrobial potential towards S. epidermidis growth and biofilm susceptibility compared to corresponding DRV liposomes, indicating the importance of MOX retention in liposomes on their activity. In conclusion, the liposome preparation method/type determines the rate of MOX release from liposomes and modulates their antimicrobial potential, a finding that deserves further in vitro and in vivo exploitation.